Factors Affecting Implementation of the Economic Stimulus Improvement Projects in Kenya (A Survey Of Selected Projects In Nairobi) - Njuguna, Francis Kariuki (My University, 2011)
The Economie Stimulus Programme (ESP) in Kenya was introduced to boost the country’s economic recovery and return the economy back to the envisioned medium term growth path, invest in iong term solutions to the challenges of food security and expand economic opportunities in rural areas for employment creation. The programme was also meant to promote equitable regional deveiopment for social stability7 This study tried to identify the factors affecting the successfì.11 implementation of the Economic Stimulus Programme and propose possible solutions to problems arising from those factors. The specific objectives of this research were to establish the effects of procurement process in the implementation of the ESP projects, to determine the effects of the contractor’s capacity to carry out the construction work on the implementation of the ESP projects, to find out the effect of the Government’s project management capacity on the implementation of the ESP Projects and to identify the effect of funding on the implementation of the ESP projects. The study used descriptive research design where 23 out of 62 projects being undertaken in Nairobi County were used as a sample representative of the entire population under study. A combination of cluster and simple random sampling procedures were used to select the sample projects. The data was collected by use of a questionnaire with structured and semi structured questions with open and closed ended questions also being used. The study utilized both qualitative and quantitative methods of data analysis after which the data was be presented using statistical tools. The study concluded that procurement process affects implementation of ESP project, as it was found that the process of procurement was tedious, was flawed, with corruption and political interferences. It also concluded that the Government’s supervisory management affects the implementation of the ESP projects, as there were low levels of supervision staff for effective supervision thus affecting the smooth performance of the contracts. From the findings and conclusion the study recommends that in order for the government to effectively implement the ESP project there is need to reduce political interference in project implementation, project procurement process and selection of contractors. This will help in the implementation of ESP project through appointment of well qualified contractors. To achieve this government needs to prepare and circulate procurement and contract supervision manuals to the grassroots levels to ensure that similar standards are applied.